1999
DOI: 10.1037/0012-1649.35.6.1462
|View full text |Cite
|
Sign up to set email alerts
|

The effects of repeated experience on children's suggestibility.

Abstract: The effect of suggestive questions on 3- to 5-year-old and 6- to 8-year-old children's recall of the final occurrence of a repeated event was examined. The event included fixed (identical) items as well as variable items where a new instantiation represented the item in each occurrence of the series. Relative to reports of children who participated in a single occurrence, children's reports about fixed items of the repeated event were more accurate and less contaminated by false suggestions. For variable items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
206
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(220 citation statements)
references
References 33 publications
11
206
1
2
Order By: Relevance
“…In one study, most of the details children reported were presented at some point over four occurrences of a repeated event and there were very few intrusions of details that were never presented. Children were confused, however, as to which details came from which occurrence, even though they remembered that they had happened (Powell et al, 1999). Yet researchers have made little progress in understanding the mechanisms that are needed to reduce such source confusions (Roberts, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, most of the details children reported were presented at some point over four occurrences of a repeated event and there were very few intrusions of details that were never presented. Children were confused, however, as to which details came from which occurrence, even though they remembered that they had happened (Powell et al, 1999). Yet researchers have made little progress in understanding the mechanisms that are needed to reduce such source confusions (Roberts, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Often source and memory accuracy are dissociated (as in studies of repeated events, e.g., Connolly & Lindsay, 2001;Powell et al, 1999); yet in other studies it seems that children can directly retrieve source (e.g., Lloyd et al, 2009). Even if source is attributed (rather than retrieved) at test, the quality of the memory trace (e.g., vividness, decay of perceptual information, lack of source-specifying information) must have some impact on subsequent source-monitoring decisions.…”
Section: Binding An Event 23mentioning
confidence: 99%
“…Research on children's source monitoring, however, raises the question of whether this standard is too high when children have experienced multiple similar events. According to source-monitoring theory and as demonstrated in the research discussed above, events that are similar and predictable can be difficult for children (and adults) to distinguish (Connolly & Lindsay, 2001;Lindsay et al, 1991;Powell et al, 1999;Roberts & Blades, 1999). Given that the nature of sexual abuse often entails similar, predictable events as indexed by children's testimony such as "it was the same as last time" or "he always does it like this" (Roberts & Powell, in press), conditions in sexual abuse cases in particular (compared to typical one-time crimes such as road traffic accidents, adbuctions) are ripe for source confusions which may seriously impede prosecution.…”
Section: Expectations Of Child Witnessesmentioning
confidence: 99%
“…Research on children's reports after multiple experiences of a similar event shows that children are often confused between the different incidents, for example, reporting a detail from one incident as if it occurred during a different one (e.g., Connolly & Lindsay, 2001;Powell, Roberts, Ceci, & Hembrooke, 1999 According to the source-monitoring framework, memories of events that are similar are more difficult to distinguish than are memories of events that are dissimilar (e.g., Johnson et al, 1993;Lindsay et al, 1991). Characteristics of target events will inevitably influence the kinds of information that are encoded in memories and, given that one method of monitoring source is assessing the qualitative characteristics of memories (Johnson et al, 1993), it is not surprising that several researchers have found that memories of similar sources are harder to distinguish from each other than are memories of dissimilar sources (Day, Howie, & Markham, 1998;Foley, Aman, & Gutch, 1987;Foley, Harris, & Hermann, 1994;Lindsay, Johnson, & Kwon, 1991;Roberts & Blades, 1999).…”
Section: The Similarity Issuementioning
confidence: 99%
See 1 more Smart Citation